(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
Cobalt Schiff base complex is widely used in many reactions such as reduction process, carbonylation of alcohol and oxidation of alkenes. Generally, this catalyst is in the powder form. It is difficult to separate the catalyst from the reaction mixture due to the small particles size of the catalyst. One way to easily separate the catalyst is by applying external magnetic field. However these catalysts would have to possess magnetic properties for this method to work on. One of the strategies to solve this problem is by adding magnetic material into the catalysts. Magnetite is a common magnetic material used as a support material which can be synthesized by the co-precipitation method of Fe2+ andFe3+. Normally, magnetite is covered by silica in order to stabilize and reduce its toxicity. This can be done by using the sol-gel approach. Silica coated magnetite is widely used as a support material because of its high surface area and easy catalyst separation after the reaction simply by applying an external magnetic field. In this research, cobalt Schiff base complex/silica@magnetite was synthesized from the condensation of cobalt (II) salicylaldehyde with 3-aminopropyltrimethoxy silane on the surface of silica@magnetite. The catalysts were characterized using Fourier transform infrared spectrometer, scanning electron microscopy and diffuse reflectance ultra-violet visible spectrometry.Â